The Influence of the Self-focusing Effect on the Optical Force Acting on Dielectric Particle Embedded in Kerr Medium - Nam, Hoang Van; Le, Cao Thanh; Quy, Ho Quang (Communications in Physics, 2013)
The influence of the self-focusing effect arised from Kerr effect on the optical force acting on the dielecric particle embedded in the Kerr medium, which is irradiated by the Gaussian beam, is proposed to concern. The expressions of the optical forces with the nonlinear refractive index and nonlinear focal length are derived. Using them, the distribution of the optical forces in the trapping region of the optical tweezer is simulated and discussed for same distinguished case of the Kerr medium with different nonlinear coefficients. The results show that the stabe region of the optical tweezer depends on the nonlinear coefficient of refractive index. Moreover, the stable region could be brokendown with a critical value of the nonlinear coefficient of refractive index of the surrounding medium irradiated by Gaussian laser pulse described by given parameters as  intensity, duration and radius of beam waist.